Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-81 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
The spinal cord injury patient Nefeli during performing hula hoop and playing at the same time with the sister/Author with a balloon. B. Nefeli during hula hoop with two rings. C. With three rings, which was possible only for a few seconds. D,F,G. Nefeli during hula hoop and swinging additionally rings with the hands.